The Language of the City as a Subject of Travel Literature: From the Late Early-Modern Period till the Turn of the 19th-20th Centuries - Диса, Катерина (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2018)
The article is focused on the aspect of communication in travel literature. Language and communication have not always constituted subject of travelers’ interest but since the 18th century travelers and guidebooks’ editors pay more attention to this framework. Examining some well-known sources, the author analyses specifics associated with the use of language in cities while travelling in foreign countries: When and why did it become relevant? About which urban practices can we learn from these sources? What kind of words and phrases did guidebooks recommend tourists to use in foreign cities?